Production, Purification And Characterization Of Poly(3- Hydroxybutyrate) P(3hb) Depolymerase Enzyme From Burkholderia Cepacia Dpi - Azami, Nor Azura (2017)
The biodegradation of polyhydroxyalkanoates (PHAs) by microbial and enzymatic methods attracts much attention since the ranges of potential applications of PHAs grow wider. However, there are limited reports on the isolation of poly(3- hydroxybutyrate) P(3HB)-degrading bacteria and detail study on the production of P(3HB) depolymerase enzyme by microorganisms from Malaysian environments.